An Innovative Approach for Online Neuroanatomy and Neurorrehabilitation Teaching Based on 3D Virtual Anatomical Models Using Leap Motion Controller During COVID-19 Pandemic - Obrero-Gaitán, Esteban; Nieto-Escamez, Francisco A.; Zagalaz-Anula, Noelia; Cortés-Pérez, Irene (Frontiers in Psychology, 2021)
After the World Health Organization had declared a pandemic of coronavirus disease (COVID-19) on March 11, 2020 many governments, including the Government of Spain, declared the state of alarm enforcing a quarantine that have left millions of students confined to their homes. This home confinement has affected students of all levels, including university students, and has forced faculties to adapt online teaching strategies. Thus, traditional classroom face-to-face teaching has suddenly been replaced by online classes. This has revealed particularly challenging for medical courses. For such purpose we have designed an online teaching proposal addressed to the Degree in Physiotherapy and the Double Degree in Nursing and Physiotherapy of the University of Jaén (Spain). The objective is to implement an online virtual teaching protocol through the use of Virtual Reality. For such a goal, the Leap Motion Controller (LMC) will be used to teach the neuroanatomy of the brain and spinal cord and to teach and practice neurorehabilitation exercises. Along with devices like the LMC students will be asked to use Health Sciences databases in order to achieve a significative learning of the course topics. The project is structured in two phases. First, students will learn neuroanatomy and neurophysiology of the most relevant neurological conditions using LMC-based models. Then, they will learn to combine LMC games and conventional physiotherapy for neurorehabilitation purposes. The work of students will include the recording of videoreports demonstrating the acquisition of neuroanatomy concepts and simulating a clinical case. With this project we will assess the usability of LMC as an educative tool, the perception, satisfaction and self-regulated learning of physiotherapy students.